A Study on Relationship Between Customer Service & Level of Customer Satisfaction with Special Reference to Banking - Agrawal, Prakash Kumar (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Since banking comes under service sector the success of banking institution depends upon satisfaction of customer. Customers are the real backbone of any banking institution until and unless the customer will not satisfied, the banking sector cannot achieved its goal. The success of banking sector so much depend upon the level of customer satisfaction. Bank provides a list of product and services to the customer. In today’s digital era, bank provide their services and product to the customer by way of digital means. Modern banking industry are using more and more technology to provide services to the customer. Keywords: Customers satisfication, relationships and banking problems.